International financial institutions and human rights: implications for public health - Thomas Stubbs; Alexander Kentikelenis (Frontiers Media S.A., 2017)
Abstract Serving as lender of last resort to countries experiencing unsustainable levels of public debt, international financial institutions have attracted intense controversy over the past decades, exemplified most recently by the popular discontent expressed in Eurozone countries following several rounds of austerity measures. In exchange for access to financial assistance, borrowing countries must settle on a list of often painful policy reforms that are aimed at balancing the budget. This practice has afforded international financial institutions substantial policy influence on governments throughout the world and in a wide array of policy areas of direct bearing on human rights. This article reviews the consequences of policy reforms mandated by international financial institutions on the enjoyment of human rights, focusing on the International Monetary Fund and World Bank. It finds that these reforms undermine the enjoyment of health rights, labour rights, and civil and political rights, all of which have deleterious implications for public health. The evidence suggests that for human rights commitments to be met, a fundamental reorientation of international financial institutions' activities will be necessary.